Biological agents and the aging brain: glial inflammation and neurotoxic signaling - Latham, Amanda S.; Moreno, Julie A.; Geer, Charlize E. (Frontiers in Aging, 2023)
Neuroinflammation is a universal characteristic of brain aging and neurological disorders, irrespective of the disease state. Glial inflammation mediates this signaling, through astrocyte and microglial polarization from neuroprotective to neurotoxic phenotypes. Glial reactivity results in the loss of homeostasis, as these cells no longer provide proper support to neurons, in addition to the production of toxic pro-inflammatory mediators. These glial changes initiate an inflammatory brain state that injures the central nervous system (CNS) over time. As the brain ages, glia are altered, including increased glial cell numbers, morphological changes, and either a pre-disposition or inability to become reactive. These alterations induce age-related neuropathologies, ultimately leading to neuronal degradation and irreversible damage associated with disorders of the aged brain, including Alzheimer's Disease (AD) and other related diseases. While the complex interactions of these glial cells and the brain are well studied, the role additional stressors, such as infectious agents, play on age-related neuropathology has not been fully elucidated. Both biological agents in the periphery, such as bacterial infections, or in the CNS, including viral infections like SARS-CoV-2, push glia into neuroinflammatory phenotypes that can exacerbate pathology within the aging brain. These biological agents release pattern associated molecular patterns (PAMPs) that bind to pattern recognition receptors (PRRs) on glial cells, beginning an inflammatory cascade. In this review, we will summarize the evidence that biological agents induce reactive glia, which worsens age-related neuropathology.